Study of hydration of sarcosine, formation of its zwitterion and their different oligomers in aqueous media: a Raman spectroscopic and theoretical study - Sharma, Poornima; Singh, Dheeraj K.; Gupta, Vineet; Asthana, B. P.; Mishra, P. C.; Singh, Ranjan K. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
{Raman spectra of the biologically important molecule sarcosine (SAR) (C3H7NO2) were studied experimentally in aqueous solution at different concentrations. These spectra were also calculated theoretically using density functional theory (DFT) at the B3LYP/6-31 1++G(d,p) level. Further, all the observed normal modes were assigned through potential energy distribution (PED). Geometry optimization of SAR produced its three conformers with slightly different energies. The lowest energy conformer of SAR was selected for a systematic solvation study wherein different numbers of water molecules (nW
Keywords: DFT calculations; Hydration; Oligomer; Raman spectra; Sarcosine; Zwitterion

Understanding the orientation of water molecules around the phosphate and attached functional groups in a phospholipid molecule: a DFT-based study - Mishra, Deepti; Das, Susanta; Krishnamurthy, Sailaja; Pal, Sourav (Molecular Simulation, 2013)
The adsorption of water molecules around a polar region (in particular around the phosphate moiety) in the phospholipid molecules is studied in this work. Phospholipid molecules with different functional groups are known to respond differently to the water molecules. Hence, we attempt to study the adsorption of water molecules around the phosphate group as a consequence of the change of functional group attached to the phosphate group, viz. phosphatidyl ethanolamine (PE), phosphatidyl choline (PC) and phosphatidyl glycerol (PG). As the latter is anionic in nature, the charge is compensated by Na+ counterion. Up to seven water molecules are adsorbed around the phosphate groups in model systems mimicking phospholipid molecule. The corresponding changes in the structural and electronic aspects are analysed. The significant difference between the PE and PC model systems is the formation of clathrate-like structure in the latter. Itisnoticed that as the number of water molecules increases to seven, both the hydrogen atoms in the water molecule participate in hydrogen bonding. However, in the PG model system, the charge-compensating counterion prevents the water molecule to form clathrate-like structures. The adsorption sites for water molecules are validated by density functional theory-based reactivity descriptors, viz. Fukui functions in the PE model system.
Keywords: cHelpG; DMPC; DMPE; DMPG; Fukui functions; Hydration

Combined effects of mutation and ionic strength onα-synuclein reveal generic features of aggregation-pronemonomeric states - Tammara, Vaishnavi; Das, Ankita; Desai, Zion; Das, Atanu (ACS Chemical Neuroscience, 2026)
alpha-Synuclein (alpha S) is a highly charged, intrinsically disordered protein (IDP) whose aberrant aggregation is linked to Parkinson's disease (PD). Along with wild-type (WT) alpha S, five single-point mutants (A30P, E46K, H50Q, G51D, and A53T) are implicated in familial PD. To resolve contradictory experimental observations under varying solution conditions, we investigated how ionic strength modulates the relative aggregation propensity of these six monomeric alpha S variants using atomistic simulations. Structural and energetic analyses at global, domain, and residue levels revealed that aggregation propensity rankings switch with increasing ionic strength but stabilize beyond physiological concentration, while A53T and H50Q consistently remain highly aggregation-prone. We additionally identified electrostatic-driven decoupling between global and local motions. Aggregation-prone monomers preferentially populate semicompact ensembles with beta-sheet propensity, an exposed and stiff N-terminus with fewer interdomain contacts, a flexible yet compact C-terminus, and an NAC domain that is either under-protected and stiff or flexible and poorly hydrated. These monomers further exhibit strong intramolecular stabilization, poor solvation, counterion binding, and subdiffusive collapsing dynamics that may facilitate intermolecular encounters. We justified aggregation propensity trends across ionic strengths, validated physiological trends using a dimer model, suggested a generic monomer-to-aggregate mechanism, and reconciled simulations with experimental variability.
Keywords: conformationallandscape; electrostatic modulation; Hydration; intrinsically disordered proteins; molecular flexibilityand compaction; polymer dynamics